First Forensic Case Report Related To Drone Accident: Case Series - Hira, Sıla Yazkan; Akar, Taner; Demirel, Birol (The Bulletin of Legal Medicine, 2018)
Drone is the most commonly used and most preferred term for the air vehicle amongst Unmanned Aerial Vehicles (UAVs). Without an on board human pilot (the person who controls drone), drones can be managed and guided from land thanks to its remote control system. The usage of drones are very versatile since they provide convenience in many areas including security, military information collection, journalism and imaging, thanks to the equipment that can be carried on it such as camera, weapon and radar. This widespread using of drones has led to the questioning of UAVs in terms of legal, social and security matters.In our study, three forensic cases due to the same drone accident were presented for the purpose of contribution to the literature. Numerous accounts of drone collisions with humans are present in the news media, though only two case have been reported in the medical literature to date...
Keywords: drone; unmanned aerial vehicle; forensic case; injury